Early Prosodic Acquisition in Bilingual Infants: The Case of the Perceptual Trochaic Bias - Bijeljac-Babic, Ranka; Höhle, Barbara; Nazzi, Thierry (Frontiers in Psychology, 2016)
Infants start learning the prosodic properties of their native language before 12 months, as shown by the emergence of a trochaic bias in English-learning infants between 6 and 9 months (Jusczyk et al., 1993), and in German-learning infants between 4 and 6 months (Höhle et al., 2009; Höhle et al., 2014), while French-learning infants do not show a bias at 6 months (Höhle et al., 2009). This language-specific emergence of a trochaic bias is supported by the fact that English and German are languages with trochaic predominance in their lexicons, while French is a language with phrase-final lengthening but lacking lexical stress. We explored the emergence of a trochaic bias in bilingual French/German infants, to study whether the developmental trajectory would be similar to monolingual infants and whether amount of relative exposure to the two languages has an impact on the emergence of the bias. Accordingly, we replicated Höhle et al. (2009) with 24 bilingual 6-month-olds learning French and German simultaneously. All infants had been exposed to both languages for 30 to 70% of the time from birth. Using the Head Preference Procedure (HPP), infants were presented with two lists of stimuli, one made up of several occurrences of the pseudoword /GAba/ with word-initial stress (trochaic pattern), the second one made up of several occurrences of the pseudoword /gaBA/ with word-final stress (iambic pattern). The stimuli were recorded by a native German female speaker. Results revealed that these French/German bilingual 6-month-olds have a trochaic bias (as evidenced by a preference to listen to the trochaic pattern). Hence, their listening preference is comparable to that of monolingual German-learning 6-month-olds, but differs from that of monolingual French-learning 6-month-olds who did not show any preference (Höhle et al., 2009). Moreover, the size of the trochaic bias in the bilingual infants was not correlated with their amount of exposure to German. The present results thus establish that the development of a trochaic bias in simultaneous bilinguals is not delayed compared to monolingual German-learning infants (Höhle et al., 2009) and is rather independent of the amount of exposure to German relative to French.